The Effect of Industrial and Recycled Steel Fibers on the Behavior of Rubberized RC Columns Under Axial Loading - Hasan A. Alasmari; Ibrahim A. Sharaky; Ahmed S. Elamary; Ayman El-Zohairy (Buildings)
The use of recycled rubber particles, in the form of crumb rubber (CR), in concrete is gaining momentum due to its environmental benefits and potential for enhancing ductility. However, the strength degradation associated with CR incorporation remains a concern. This study investigates the compressive and axial behavior of reinforced concrete columns incorporating CR and hybrid steel fibers, comprising recycled steel fibers (RSFs) and copper-coated micro steel fibers (MSFs). Sixteen circular columns with varying CR contents (0–20%) and a constant fiber dosage (0.7% RSF and 0.3% MSF by volume) were cast and tested under axial compression. The results showed that CR reduced compressive strength, while the addition of hybrid fibers significantly improved strength, ductility, and energy absorption. Columns with up to 8% CR and fibers demonstrated comparable or superior load-bearing capacity to conventional concrete. Finite element modeling using ABAQUS software (Version 6.9) validated the experimental results, with numerical predictions closely matching load–displacement behavior and failure modes. This study highlights the potential of using CR and hybrid steel fibers in structural concrete to promote sustainability without compromising performance.